Developing E-Learning Based English Materials With The Insertion of Balinese Culture for the Eleventh Grade Students of Food and Beverage Service Department at SMK N 2 Singaraja - ., Kadek Puji Wedayani; ., Prof. Dr. Putu Kerti Nitiasih, MA; ., I Putu Ngurah Wage M, S.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2017)
Penelitian ini merupakan penelitian dan pengembangan (R&D) yang bertujuan untuk: (1) mengidentifikasi jenis materi bahasa Inggris dan budaya Bali yang dibutuhkan oleh siswa kelas sebelas Jurusan Tata Hidang di SMK N 2 Singaraja; (2) mengidentifikasi desain materi bahasa Inggris untuk siswa Jurusan Tata Hidang dengan insersi budaya Bali dalam bentuk e-learning; (3) mengidentifikasi kualitas dari materi untuk siswa Jurusan Tata Hidang dengan insersi budaya Bali dalam bentuk e-learning. Penelitian ini dilakukan berdasarkan pada desain penelitian dan pengembangan oleh Lee & Owens (2004). Data penelitian dikumpulkan melalui observasi, angket, wawancara dan uji ahli. Hasil data dari observasi, angket, dan wawancara dianalisis dengan menggunakan analisis deskriptif, dan data dari uji ahli dianalisis menggunakan Interrater Agreement Model. Hasil penelitian menunjukan bahwa (1) siswa membutuhkan materi bahasa inggris dengan insersi budaya Bali yang mencakup tujuh unit, dan didukung oleh infrastruktur dari sekolah; (2) desain materi bahas Inggris dengan insersi budaya Bali untuk siswa Jurusan Tata Hidang di SMK N 2 Singaraja berdasarkan kebutuhan; (3) materi bahasa inggris dengan insersis budaya Bali untuk siswa jurusan Tata Hidang dikategorikan sebagai materi berkualitas tinggi berdasarkan validasi isi, tanggapan dari guru dan siswa, dan skoring rubrik. Kata Kunci : R & D, siswa Jurusan Tata Hidang, materi Bahasa inggris. This study was a Research and Development (R&D) study which aimed at: (1) identifying kind of English materials and Balinese culture are needed by the eleventh year students majoring in Food and Beverage Service Department at SMK N 2 Singaraja; (2) identifying the design of English materials for Food and Beverage Service Department with the insertion of Balinese culture in the form of E-learning; (3) identifying the quality of the materials for Food and Beverage Department with the insertion of Balinese culture in the form of e-learning. This study was conducted based on the research and development design proposed by Lee and Owens (2004). The data of the study were collected through observation, questionnaire, interview and expert judge. The results of the data from observation, questionnaire, and interview were analyzed by using descriptive analysis, and the data from expert judge was analyzed by using interrater agreement model. The result of the study showed that (1) the students needed English materials and Balinese culture developed in seven units, and supported by the infrastructure from the school; (2) the design of the English materials for Food and Beverage department students was developed based on the needs; (3) the English materials for Food and Beverage department students was categorized as high quality materials based on content validity, teachers’ and students’ response, and scoring rubric.keyword : R & D, Food and Beverage Service department students, English materials